Penyuluhan Pengelolaan Sampah dengan Metode Pemilahan di Sukahati, Kabupaten Bogor - Mohamad Hery Saripudin; Syahrul Salam; Aan Setiadarma; Yuliani Widianingsih (CV. Multi Kreasi Media, 2025)
This counselling aims to increase participants' knowledge and awareness regarding household waste sorting practices. Negligent behaviour towards waste sorting impacts the mixing of waste and can lead to the accumulation of waste that is not managed properly. This can cause waste problems in the area, so active community participation to help sort waste from the household level is very much needed. The community service carried out this time is counselling that takes place bravely. The participants involved are residents of the Sukahati area, Bogor Regency. The counselling is also supported by tracing the participants' understanding using pre-test and post-test questionnaires. Based on this service, the community service team has made efforts to increase participants' knowledge regarding awareness and knowledge of participants regarding waste sorting.